Augmented Reality dan Virtual Reality dalam Meningkatkan Pemahaman Konsep Peserta Didik: Tinjauan Literatur Sistematis - Yeni Sulastri (Suria Academic Press, 2026)
The rapid advancement of digital technology has accelerated the adoption of immersive learning technologies, particularly Augmented Reality (AR) and Virtual Reality (VR), as innovative tools for facilitating conceptual learning. However, empirical findings regarding their effectiveness in improving students' conceptual understanding remain inconclusive. This study aimed to systematically examine the potential, effectiveness, and implementation challenges of AR and VR in enhancing conceptual understanding across educational settings. A Systematic Literature Review (SLR) was conducted following the PRISMA 2020 guidelines. Literature was retrieved from Scopus, Web of Science, ScienceDirect, SpringerLink, ERIC, and Google Scholar, covering publications from 2015 to 2025. Of the 436 studies initially identified, 36 peer-reviewed articles met the inclusion criteria and were synthesized using thematic analysis. The findings indicate that AR and VR consistently improve concept visualization, learning motivation, student engagement, and immersive learning experiences. Nevertheless, their impact on conceptual understanding varies depending on instructional design quality, pedagogical integration, learners' characteristics, and cognitive load management. Furthermore, implementation barriers including infrastructure limitations, technology costs, teachers' digital competence, and unequal access to technological resources continue to constrain the effective adoption of immersive technologies. The review suggests that successful implementation of AR and VR depends not merely on technological sophistication but on the alignment of technology with sound pedagogical principles and contextual learning needs. These findings contribute to the theoretical development of immersive learning research and provide practical recommendations for educators, instructional designers, and policymakers seeking to optimize AR and VR integration in educational environments.